Utilization of ?Alugbati? (Basella alba L.) Leaves Powder to Increase Vitamin A Content of Fresh Egg Noodles. - Soriano, Pamela C.; Villame, Rovi Gem E.
In the Philippines, indigenous vegetables like ?alugbati? (Basella alba L.) can be utilized to address micronutrient deficiencies, such as vitamin A deficiency (VAD). This study aimed to develop fresh egg noodles with higher vitamin A content through the utilization of ?alugbati? leaves powder. Powder from ?alugbati? leaves was produced through dehydration of fully expanded leaves. The resultant powder was used to create three formulations of fresh egg noodles at 10%, 15%, and 20% substitution levels, with 100% wheat flour serving as the control. All formulations and the control were subjected to a water disintegration test and preference ranking test. The most preferred formulation was further evaluated for proximate composition, total carotenoid content (TCC), color, physical characteristics, and consumer acceptability. Data from triplicate experiments were statistically analyzed (p ≤ 0.05). Results showed that all samples were resistant to water disintegration (20 min in boiling water) and egg noodle with 15% substitution level was the most preferred. This sample had significantly higher ash (2.27 ± 0.28), fiber (1.77 ± 0.38), and protein (11.50 ± 0.11) contents than the control. A significantly higher TCC (1550 µg/g) compared to the control (610 µg/g) also signified that substituting with ?alugbati? leaves powder increased the vitamin A content of the noodles. From this, consuming 5?10 g of ?alugbati? egg noodles will be able to provide the vitamin A requirement of 400?800 µg retinol equivalent (RE). The egg noodles with a 15% substitution level also had a significantly darker green color and significantly lower elasticity. Moreover, this formulation was generally acceptable with mean Hedonic scores ranging from 7.20 (Like Moderately) to 7.80 (Like Very Much). This study demonstrated that fresh egg noodles with ?alugbati? leaves powder can be a good source of vitamin A. Clinical studies should be conducted to determine the role of the product in alleviating VAD especially in children and pregnant women.